PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Estuti Fitri Hartini; Kartika Hernapuri Rosadi (Jurnal Manajemen Kewirausahaan, 2019)
This research is meant to find out the influence of Price Earnings Ratio, Return on Equity, Debt to Equity Ratio, and Current Ratio to the stock price of food and beverages companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. The  samples of this research are food and beverages company that being active are traded and listed in Indonesia Stock Exchange 2013-2017. Moreover, it is chosen by purposive sampling whereas it is based on some criteria. The analysis method used to test on the research hypothesis is regression. The result shows that Price Earnings Ratio (PER) have influence significant to the stock price with positif away, Return on Equity (ROE) have influence to significant the stock price with positif away, Debt to Equity Ratio (DER) is not signifcant to the stock price, and Current Ratio (CR) is not signifcant to the stock price. Kata Kunci: PER, ROE, DER, CR, Stock Price